Fusarium endophyticum sp. nov. (Nectriaceae, Hypocreales), a new endophytic fungus from northern Thailand - Suwannarach, Nakarin; Khuna, Surapong; Kumla, Jaturong; Thitla, Tanapol; Hongsanan, Sinang; Nuangmek, Wipornpan; Lumyong, Saisamorn (Phytotaxa, 2023)
A new endophytic ascomycete, described herein as Fusarium endophyticum, was isolated from leaves of Camellia sinensis var. assamica collected from Nan Province, northern Thailand. This species is described using morphological characteristics and molecular multi-gene analyses. Multi-gene phylogenetic analyses of a combination of internal transcribed spacer region of the rDNA (ITS), translation-elongation factor 1 alpha (tef-1), RNA polymerase II second largest subunit (rpb2), and RNA polymerase II largest subunit (rpb1) genes revealed that F. endophyticum belonged to the Fusarium lateritium species complex (FLSC) and was distinct from all other known species. A full description, illustrations and a phylogenetic tree showing the position of F. endophyticum are provided.